2023
DOI: 10.31083/j.jin2202038
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the Gut Microbiota on Alzheimer's Disease: A Narrative Review

Abstract: Alzheimer's disease (AD) is a common neurodegenerative disease that tends to occur in the elderly. The main symptom is hypomnesia. More and more older people are suffering from this disease worldwide. By 2050, 152 million people worldwide are expected to have AD. It is thought that the aggregation of amyloid-beta peptides and hyper-phosphorylated tau tangles contribute to AD. The microbiotagut-brain (MGB) axis appears as a new concept. The MGB axis is a collection of microbial molecules produced in the gastroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 180 publications
0
4
0
Order By: Relevance
“…Recent evidence also indicates that resident microbes of the human gastrointestinal (GI)-tract microbiome have the potential to provide a life-long supply of microbial-derived neurotoxins including bacterial amyloids and RNA, glycolipids including lipopolysaccharide (LPS), and other potent endotoxins that appear to have significant and deleterious effects on brain miRNA complexity and which contribute to altered gene expression signaling in the AD brain [ 31 , 50 , 51 , 107 , 108 , 109 , 110 ];…”
Section: Specific Features Of Mirna Abundance Speciation and Traffick...mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent evidence also indicates that resident microbes of the human gastrointestinal (GI)-tract microbiome have the potential to provide a life-long supply of microbial-derived neurotoxins including bacterial amyloids and RNA, glycolipids including lipopolysaccharide (LPS), and other potent endotoxins that appear to have significant and deleterious effects on brain miRNA complexity and which contribute to altered gene expression signaling in the AD brain [ 31 , 50 , 51 , 107 , 108 , 109 , 110 ];…”
Section: Specific Features Of Mirna Abundance Speciation and Traffick...mentioning
confidence: 99%
“…The now well documented obvious importance of a global disruption in miRNA signaling in the AD-affected brain currently suggests that blocking or modulating miRNA abundance or the transcription factors such as the NF-kB p50/p65 complex that regulates miRNA generation may have some therapeutic value [ 5 , 7 , 9 , 12 , 26 , 30 , 37 ]. To this end a number of stabilized anti-miRNA (AM; antogomir), sense-RNA and anti-sense RNA-based oligonucleotide strategies have been proposed as novel therapeutic agents in the clinical management of AD [ 28 , 29 , 76 , 79 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 ]. The major problem using these types of approaches are: (i) the extreme heterogeneity of AD onset, neuropathology and disease course among individual AD patients; and (ii) the fact that miRNAs and the transcription factors that regulate them (such as the pro-inflammatory dimeric NF-kB p50/p65 complex) have both multiple and complicated off-target effects [ 28 , 37 , 39 , 112 , 113 , 114 ].…”
Section: Targeting Mirna For Ad Treatment and Related Therapeutic Str...mentioning
confidence: 99%
“…Recent studies have shown that these products modify the intestinal microbiota and improve cognitive functioning through the expression of neurotransmitter receptors and neuromodulators [307]. Specifically, studies in animal models showed inhibition of oxidative stress and cell apoptosis.…”
Section: Prebiotics and Probioticsmentioning
confidence: 99%
“…Recent studies have shown that the gut microbiota can affect the development of Alzheimer's disease (AD) through various mechanisms, including neuroinflammation, amyloid-beta (Aβ) deposition, and tau protein accumulation. The gut microbiota can affect AD through several pathways, including the modulation of neurochemical and neurometabolic pathways, synthesis and secretion of neurotrophic factors, and the production of microbial molecules that influence brain function [1].…”
Section: Introductionmentioning
confidence: 99%